Comparing the Use of Multimedia and Teaching in Small Groups for Teaching of Anterior Tooth Preparation with Layered Technique - Fatemeh Esmi; Atefeh Saffari; Elnaz Mirzaee; Mryam Ehsani (Babol University of Medical Sciences, 2014)
BACKGROUND AND OBJECTIVE: The traditional methods of teaching that are currently running do not alone meet the rapid growth of information and knowledge and the changing needs of societies. Knowing different methods of teaching and use of learning aids, will help teachers and students to heighten the steps toward making a difference in education. The aim of this study was to determine the effectiveness of an educational multimedia in teaching process. Methods: This study was performed on 30 dental students of the 6th semester of Babol dental school on the academic year of 2012-13. Students were divided into two equal groups and matched. Two groups were taught based on the traditional training method and the multimedia presentation. Their awareness was analyzed with the paired-T-test and the Independent-T-test according to the pre- test and the post-test scores. Findings: The mean scores of before and after the lecture in the lecture groups, were respectively (5/06 ± 1/9) and (9/93 ± 1/7), and the second group mean scores before and after viewing the educational multimedia, were (4/13 ± 1/4) and (10/33 ± 1/2), respectively. Paired-T-test showed that the mean of before and after scores for each experimental group significantly increased (P0/05). Conclusion: We can conclude that an educational multimedia of the tooth restoration can be used successfully to increase the knowledge of dental students.